Cannabis sativa and/or melatonin do not alter brain lipid but alter oxidative mechanisms in female rats - Halimat Amin Abdulrahim; Isiaka Abdullateef Alagbonsi; Oluwasola Amuda; Noah Adavize Omeiza; Abdul-Rahuf Aderemi Feyitimi; Luqman Aribidesi Olayaki (BMC, 2021)
Abstract Background Lipid profile and redox status play a role in brain (dys)functions. Cannabinoid and melatonergic systems operate in the brain and contribute to brain (patho)physiology, but their roles in the modulation of brain lipid and redox status are not well-known. We studied the effect of ethanol extract of Cannabis sativa (CS) and/or melatonin (M) on the lipid profile and anti-oxidant system of the rat brain. Methods We randomly divided twenty-four (24) female Wistar rats into 4 groups (n = 6 rats each). Group 1 (control) received distilled water mixed with DMSO. Groups II-IV received CS (2 mg/kg), M (4 mg/kg), and co-administration of CS and M (CS + M) respectively via oral gavage between 8:00 am and 10:00 am once daily for 14 days. Animals underwent 12-h fasting after the last day of treatment and sacrificed under ketamine anesthesia (20 mg/kg; i.m). The brain tissues were excised and homogenized for assay of the concentrations of the total cholesterol (TC), triacylglycerol (TG), high-density lipoprotein cholesterol (HDL-C), nitric oxide (NO), malondialdehyde (MDA), and the activities of glucose-6-phosphate dehydrogenase (G6PD), glutathione reductase (GR), glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), and acetylcholinesterase (AChE). One-way analysis of variance (ANOVA) was used to compare means across groups, followed by the least significant difference (LSD) post-hoc test. Results CS and/or M did not affect the lipid profile parameters. However, CS increased the G6PD (from 15.58 ± 1.09 to 21.02 ± 1.45 U/L; p = 0.047), GPx (from 10.47 ± 0.86 to 17.71 ± 1.04 U/L; p = 0.019), and SOD (from 0.81 ± 0.02 to 0.90 ± 0.01 μM; p = 0.007), but decreased NO (from 9.40 ± 0.51 to 6.75 ± 0.21 μM; p = 0.010) and had no effect on MDA (p = 0.905), CAT (p = 0.831), GR (p = 0.639), and AChE (p = 0.571) in comparison with the control group. M augmented the increase in G6PD (from 21.02 ± 1.45 U/L to 27.18 ± 1.81 U/L; p = 0.032) and decrease in NO (from 6.75 ± 0.21 to 4.86 ± 0.13 μM; p = 0.034) but abolished the increase in GPx (from 17.71 ± 1.04 to 8.59 ± 2.06 U/L; p = 0.006) and SOD (from 0.90 ± 0.01 to 0.70 ± 0.00 μM; p = 0.000) elicited by CS in the rat brain in comparison with the CS group. Conclusions CS and M do not alter brain lipid profile. Our data support the contention that CS elicits an anti-oxidative effect on the brain tissue and that CS + M elicits a pro-oxidant effect in rat brain.